Empire, power, and indigenous elites : a case study of the Nehemiah memoir - Fitzpatrick-McKinley, Anne. (Supplements to the Journal for the Study of Judaism, 2015)
Ancient Near Eastern empires, including Assyria, Babylon and Persia, frequently permitted local rulers to remain in power. The roles of the indigenous elites reflected in the Nehemiah Memoir can be compared to those encountered elsewhere. Nehemiah was an imperial appointee, likely of a military/administrative background, whose mission was to establish a birta in Jerusalem, thereby limiting the power of local elites. As a loyal servant of Persia, Nehemiah brought to his mission a certain amount of ethnic/cultic colouring seen in certain aspects of his activities in Jerusalem, in particular in his use of Mosaic authority (but not of specific Mosaic laws). Nehemiah appealed to ancient Jerusalemite traditions in order to eliminate opposition to him from powerful local elite networks.